Tree‐ring‐based SPEI reconstruction in central Tianshan Mountains of China since A.D. 1820 and links to westerly circulation. (5th October 2016) - Jiang, Peng; Liu, Hongyan; Wu, Xiuchen; Wang, Hongya
ABSTRACT: Understanding long‐time scale of drought variability is vital to the hydrological management and agriculture in dryland. Based on two sites of Schrenk spruce ( Picea schrenkiana ), a robust tree‐ring chronology was developed and employed to study the drought variability in central Tianshan Mountains. The result shows that the chronology significantly positively correlates with precipitation in previous December, April, May and June in current year, and significantly negatively correlates with temperature in April, May, July and August in current year. Highest correlation was found between tree‐ring width and both April–June standardized precipitation evapotranspiration index (SPEI) and Palmer drought severity index, indicating that Schrenk spruce's growth strongly responds to the current summer drought. We further reconstruct SPEI for the period 1820–2005, and the series are verified both with the statistical methods and other nearby reconstructions. Multi‐taper method spectral and wavelet analyses reveal the significant low‐ and high‐frequency cycles (26–36, 8.5, 6.0, 5.7 and 3.4 years). Drought has alternatively varied in the past two centuries with four apparently dry periods and wet periods, and the driest period occurs from 1870 to 1890 and the wettest period occurs from 1842 to 1855 in the central Tianshan Mountains. Some extreme drought events are detected, such as 1885, 1918, 1944–1945 and 1951. Significant correlations of reconstructed SPEI and precipitation and temperature indicate that the source of air masses and the water vapour transport paths lies in the northwestern direction of our study area and are controlled by westerly circulation. This SPEI reconstruction provides a long‐term drought history in the central Tianshan Mountains and can serve as scientific basis for water resources management in this semi‐arid region.